EVALUASI PELAKSANAAN PENDIDIKAN PESANTREN MINI DI MADRASAH ALIYAH PATRA MANDIRI PLAJU PALEMBANG - Miswanto, Miswanto (El-Idare: Journal of Islamic Education Management, 2016)
Evaluation of educational programs is a process to determine whether the purpose of education can already be realized. This study raised the question of the evaluation of education programs in mini schools Plaju MA Patra Mandiri Palembang. Program Pesantren mini itself is an education that adopts the education system in schools in general, but only a small portion is applied. In conducting the research, the evaluators use this type of model evaluation CIPP (context, input, process, product). The goal is to determine the extent to which the program is running properly. This type of research is the evaluation of a program that uses the model CIPP, namely: contex, input, process and product, with a qualitative approach to the subject of the research is the principal, waka curriculum, waka student, teachers, administrators, and the community around MA Patra Mandiri Plaju Palembang. Data collection techniques in this research is to use observation, interviews and documentation, while for analyzing the data using three procedures, namely data reduction, display, and data verification.